Two Years for an English Teacher to Become a Novice Educational Researcher: Author’s Experiences from Writing Opinion Articles to Research Articles - Sereyrath Em (MASI Mandiri Edukasi, 2023)
The current study employs an autobiographical design. An autographical design is a type ofÂ qualitativeÂ approach affiliated with the social explanatory paradigm of research. The author of this article collected his published work, certificates of achievement, and degrees to present as the results of this study. He also used the memorization of his training, workshops, and seminars to present the findings. The results show that from July 2021, the author has upgraded himself from an English teacher to become a novice educational researcher, and his work has been concerning the English language and educational fields. Additionally, he presented how he became a researcher including the difficulties, challenges, and opportunities he experienced in his life over the last two years. He noted that English for teaching and learning is not the same as English for writing research articles. He also encouraged other teachers to engage in research since it is not as difficult as everyone might have expected, and it is the best way to solve the existing problems in all fields including learning and teaching. Besides, research is not only to solve problems but to improve the outcome of the process of learning and teaching as well as other concerning areas. He finally showed simple and easy ways that everyone could become researchers and how to get their work published.